Evaluation and opportunities in overtraining approaches - Roose, J.; de Vries, W. R.; Schmikli, S. L.; Backx, F. J. G.; van Doornen, L. J. P. (Research Quarterly for Exercise and Sport, 2009)
Overtraining (OT) as a sports phenomenon can be caused by stressors on various levels (physical, emotional, psychological, and social) and evokes responses on these levels. This study evaluated research and new opportunities in the field of OT by introducing an integrated multidisciplinary approach, based on the single and multistressors approach. The single stressor approach focuses on the training load-recovery imbalance, which results in a stagnating performance, excluding the etiology by nonsport-related factors. The multistressors approach includes all factors as relevant in the etiology of a stagnating performance. In future studies on OT, an integrative approach should not only highlight changes in training regimes and specific responses to training stressors but also focus on the role of training-related recovery, the impact of stressors, and personality factors influencing stress appraisal. This will provide a better insight into the etiology and consequences of OT, necessary for prevention and treatment in sport practice, and enhance the focus on adequate recovery (good sleep, sufficient rest periods) and athletes' stress-related responses.